Gross and Morphological Studies on Adrenal Gland of The Large White Yorkshire Pig - Panwar, Aruna (Indian Journal of Veterinary Anatomy, 2020)
The present investigation was carried out on 12 pairs of adrenal glands from recently slaughtered pigs of both genders of 6-12 months age group. The adrenals were situated at the cranio medial aspect of the kidney embedded in peri-renal fat. These were elongated structures which were reddish brown in colour. Left adrenal gland was larger and heavier than the right one. Statistical differences between right and left adrenals for all values analyzed were observed. The difference between right and left adrenal volume, weight and length were statistically significant.